Implementasi Manajemen Modern dalam Mewujudkan Good University Governance - Usman, Usman (Jurnal Manajemen Bisnis dan Keuangan, 2024)
Good University Governance (GUG) is an approach to higher education management that prioritizes transparency so that responsibility to society can be better measured. This research evaluates how the GUG concept is applied in higher education management and how the implementation process takes place effectively. The research method used is a literature study, with sources of information based on literature reviews such as books, journal articles, and other relevant materials. The research results show that the GUG concept is suitable for application in higher education management and aligns with modern management principles. However, this research has limitations because it needs to compare the best practices implemented by universities or identify the obstacles they may face.